Final Fusion in Patients Treated with Rib Based Distraction: A Review of Peri-Operative Results. Issue 1 (April 2016) - Heflin, John; Morgan, Jessica; Heagy, Victoria; Smith, John
Introduction: Rib based distraction for early onset scoliosis (EOS) and thoracic insufficiency is an accepted form of managing progressive spinal and chest wall deformities. Once growth has ceased, these patients generally undergo definitive fusion surgery to prevent further progression of deformity. Our objective was to review peri-operative outcomes in patients undergoing definitive fusion following rib-based distraction treatment for EOS. Methods: 27 patients treated with rib-based distraction for EOS who subsequently underwent final fusion were evaluated with an IRB approved patient registry. All patients were treated by a single surgeon. Information from the registry, patient operative reports, and X-rays were reviewed. Surgical time, blood-loss, complications, overall correction, and need for osteotomies were documented. Radiographic measurements included pre and post-operative sagittal and coronal Cobb angles. All numerical measurements were evaluated for statistical mean, range, and standard deviation. Results: The average age at implantation of the rib-based construct was 7.45 (1.78–11.78) years. The mean age at definitive fusion was 13.51 (9.21–18.51) years, following an average of 10.5 (0–18) lengthening procedures and 13.35 (3–21) total surgeries. The mean coronal Cobb angle measured 67.42 (40–107) degrees prior to fusion and 50.17 (32–82) degrees following fusion. Pre-operative mean kyphosis was 61.08 (8–113) degrees and post-operatively averaged 50.00 (20–85) degrees. Operative time averaged 256 (115–520) minutes with a mean 534 cc (180–1280) blood loss. Osteotomies were required in 11 patients (41%). Complications occurred in 12 patients (44%), 9 requiring a repeat procedure. Conclusion: Definitive fusion in patients treated with rib-based distraction is both technically challenging and tends to be associated with longer operative times, higher blood loss, and a higher rate of complications. Although the amount of correction is limited by stiffness, scaring, and autofusion, definitive fusion surgery does improve pre-operative coronal Cobb angles and kyphosis. Longer term studies will be needed to establish whether correction is maintained over time.